High genetic diversity and connectivity in Colossoma macropomum in the Amazon basin revealed by microsatellite markers - Paola Fazzi-Gomes; Sávio Guerreiro; Glauber David Almeida Palheta; Nuno Filipe Alves Correa de Melo; Sidney Santos; Igor Hamoy (Genetics and Molecular Biology)
Abstract Colossoma macropomum is the second largest scaled fish of the Amazon. It is economically important for commercial fisheries and for aquaculture, but few studies have examined the diversity and genetic structure of natural populations of this species. The aim of this study was to investigate the levels of genetic variability and connectivity that exist between three natural populations of C. macropomum from the Amazon basin. In total, 247 samples were collected from the municipalities of Tefé, Manaus, and Santarém. The populations were genotyped using a panel of 12 multiplex microsatellite markers. The genetic diversity found in these populations was high and similar to other populations described in the literature. These populations showed a pattern of high gene flow associated with the lack of a genetic structure pattern, indicating that the number of migrants per generation and recent migration rates are high. The values of the FST, RST, and exact test of differentiation were not significant for pairwise comparisons between populations. The Bayesian population clustering analysis indicated a single population. Thus, the data provide evidence for high genetic diversity and high gene flow among C. macropomum populations in the investigated region of the Amazon basin. This information is important for programs aiming at the conservation of natural populations.